Pengaruh Kinerja Lingkungan, Tipe Industri, Green Innovation, Ukuran Perusahaan Dan Kepemilikan Asing Terhadap Environmental Disclosure Di Perusahaan Manufaktur - Ernanda Sartika Putri; Aji, Nur Prasetyo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Modern economics today not only focuses on the financial performance of companies but also on their responsibility towards the surrounding social environment. This condition has led to an increasing demand for transparency regarding the environmental impact of corporate activities. This study aims to analyze the effect of environmental performance, industry type, green innovation, company size, and foreign ownership on environmental disclosure in manufacturing companies listed on the Indonesia Stock Exchange during the period 2021-2023. This research uses a quantitative method and multiple linear regression analysis. The study found that environmental performance, industry type, and green innovation do not have a significant effect on environmental disclosure, while company size has a significant impact. Foreign ownership also does not influence Environmental Disclosure. This research contributes to the understanding of the factors affecting corporate environmental transparency.